NATALIYA REVONYUK: VISUAL RESONANCE AS A CONTEMPORARY SACRED LANGUAGE IN ART - Fedorenko, Iryna (Collection of scientific papers «ΛΌГOΣ», 2025)
Ukrainian artist Nataliya Revonyuk represents a unique phenomenon in the field of contemporary visual art. Her artistic method, described as 'visual resonance,' is a synthesis of meditative energy, graphic precision, and transcendental symbolism. Rather than simply being viewed, her works are experienced as energetic transmissions—what she herself refers to as 'soul keys.